The regeneration of Oriental beech (Fagus orientalis Lipsky) share in the secondary hornbeam stands using the complex cutting - Аydin B. Yakhyaev; Elshad M. Gurbanov; Vahid S. Farzaliyev; Farid S. Seyfullayev (Journal of Forest Science, 2021)
In the paper, the results of the complex cuttings were presented in the secondary hornbeam stands with the aim of regenerating the natural beech stands in the northern regions of Azerbaijan. For this purpose, three complex cutting procedures were carried out with a recurrence at 5 and 10 years in four sites of the secondary hornbeam stands in the northern regions. The experimental plots were characterised with: a stand density of 0.5-0.7, the age of the forest stands of 60-130 years, undergrowth of 12-25 years, a stand volume of 130-200 m3.ha-1, the beech percentage in the composition of stands of 17-28%, hornbeam 62-79% spread over the southern and northern slopes of the mountains. As a result of the complex cuttings, the share of beech trees in the composition of the parent stands increased 2.2-3.0 times. During cutting, the share of beech trees, as a part of undergrowth, increased 3.8-4.3 times. Based on the data, mathematical models were established reflecting the dynamics of the numbers of the undergrowth and the total stand volume of the forest stands depending on the participation percentage of beech trees in the parent stand.